Advances in Transdermal Drug Delivery Systems for Systemic Disease Management - Pheny Laurn; Much Arean (Journal of Advanced Pharmaceutical Research Sciences and Sustainability (JAPRSS), 2025)
Background: Transdermal drug delivery systems (TDDS) have emerged as a promising alternative to conventional drug administration routes for systemic disease management. These systems offer several advantages, including improved patient compliance, steady drug release, and avoidance of gastrointestinal metabolism. Recent technological advancements have further enhanced the efficacy and applicability of TDDS, making them a viable option for a wide range of therapeutic applications. Objective: This study aims to review the recent advances in TDDS, focusing on new technologies, materials, and formulations that have improved drug delivery efficiency and patient outcomes in systemic disease management. Methods: A comprehensive literature review was conducted, covering scientific articles published between 2015 and 2023. The study examined various aspects of TDDS, including the types of drugs delivered, the materials used for transdermal patches, and the innovations in delivery mechanisms. Data was collected on the clinical efficacy, safety profiles, and patient adherence associated with these systems. Results: The review identified significant advancements in TDDS, such as the development of microneedles, iontophoresis, and ultrasound-enhanced delivery systems. These technologies have improved drug permeability through the skin, enabling the effective delivery of larger molecules and peptides. Additionally, new materials, such as bioadhesive polymers and hydrogel matrices, have enhanced the stability and comfort of transdermal patches. Clinical studies reported positive outcomes in patient adherence and therapeutic efficacy, particularly in managing chronic conditions like hypertension, diabetes, and pain. Conclusion: Recent advancements in TDDS have significantly broadened their therapeutic scope, making them an increasingly attractive option for systemic disease management. The integration of innovative technologies and materials has improved drug delivery efficiency and patient experience. Future research should focus on further optimizing these systems and expanding their applications to more complex therapeutic areas.